Pengaruh Model Pembelajaran Snowball Throwing Terhadap Kemampuan Membuat Kalimat Pada Pembelajaran Bahasa Indonesia Kelas IV SD - Septiani; Hetilaniar; Syska Purnama Sari (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the effect of the Snowball Throwing learning model on ability to make sentences in indonesian language learning of grade IV elementary school students. The background of this study is based on the low ability to make sentences that are in accordance with the structure and rules of the Indonesian language, as well as the lack of student activity in the learning process. This study uses a quantitative method with an experimental design of the pretest-posttest control group design type. The subjects of the study were grade IV students of SDN 7 Banyuasin 1 in the 2024/2025 academic year consisting of two classes, namely the experimental class(using the snowball throwing model) and the control class (using convenntional learning), each consisting of 331 student. The instruments used were multiple choice and essay test, with validity and realibility that have been tested using SPSS 25. The result of data analysis showed that the data were normally distributed and homogeneous. Hypothesis testing using the t-test obtained a ta value at a significance level of 0,05. So Ho was rejected and Ha eas accepted. This means that there is a significant influence of the snowball throwing learning model on i proving students’ sentences-making abilities. Thus , the snowball throwing model can be used as an alternative learning strategy that is fun and increasees students’ activiness and language skill.